PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, MUSYARAKAH, IJARAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2016-2018 - Oryza Sativa Meiswari; Diah Nurdiwaty (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
Profitability is a certain condition that has been achieved by a sharia bank as a reflection of public trust in commercial banks that have undergone a process of activity for several years. This study aims to analyze the effect of murabahah, mudharabah, musyarakah and ijarah financing on the profitability of Islamic commercial banks. Profitability is the dependent variable in this study, while murabahah, mudharabah, musyarakah and ijarah financing are independent variables.The type of data used is secondary data which is obtained from quarterly financial reports taken from the official website or website www.bi.go.id/www.ojk.go.id and the official website of each Islamic Commercial Bank. The study population consisted of 12 Islamic commercial banks, and obtained 72 samples by purposive sampling method. The approach used in this research is a quantitative approach. The data analysis technique used is multiple linear regression.The results of this study indicate that partially murabahah financing and ijarah financing have a significant effect on profitability. Based on the results of the F test, the variables of murabahah, mudharabah, musyarakah and ijarah financing simultaneously have a significant effect on profitability.